2020
DOI: 10.1037/ppm0000208
|View full text |Cite
|
Sign up to set email alerts
|

Once upon a game: Exploring video game nostalgia and its impact on well-being.

Abstract: Retro gaming and the renaissance of past video games has been an emerging area of interest for media research within the past years. Yet, there is little empirical research trying to explain the psychological effects and benefits of past-related gaming. This article explores how remembering of past video game experiences relates to nostalgia, a mixed emotion elicited via reflection on the past that shows positive associations to well-being. To this end, a mixed-methods approach was used to investigate prerequi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 75 publications
4
40
0
Order By: Relevance
“…Our findings are also in line with research demonstrating nostalgia to be elicited by media content: Besides music (Barrett et al, 2010), film-and video game trailers (Natterer, 2014), and reminiscences of media used in the past (Wulf, Bowman et al, 2018, the current study provides evidence that actual video game play can elicit nostalgia. This finding suggests that nostalgia elicited by anticipating game play, as well as actual game play, is associated with personal meaning.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings are also in line with research demonstrating nostalgia to be elicited by media content: Besides music (Barrett et al, 2010), film-and video game trailers (Natterer, 2014), and reminiscences of media used in the past (Wulf, Bowman et al, 2018, the current study provides evidence that actual video game play can elicit nostalgia. This finding suggests that nostalgia elicited by anticipating game play, as well as actual game play, is associated with personal meaning.…”
Section: Discussionsupporting
confidence: 90%
“…Nostalgic experiences are characterized by recalling positive, meaningful events from the past that were typically experienced with close others (Wildschut, Sedikides, Arndt, & Routledge, 2006). Nostalgia can be triggered by psychological threats such as boredom (van Tilburg, Igou, & Sedikides, 2013), loneliness (Wildschut et al, 2006), meaninglessness (Routledge et al, 2011), or threats to authenticity (Baldwin, Biernat, & Landau, 2015), and incidental experiences such as smells (Reid, Green, Wildschut, & Sedikides, 2014), music (Cheung et al, 2013), movies, video game trailers (Natterer, 2014), and memories of playing games (Wulf, Bowman, Velez, & Breuer, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Within the action genre, we observed that three out of six categories with the most significant increase in SL (Rust, Call of Duty: Modern Warfare, DayZ) were shooter video games with either a survival setting (Rust, DayZ) or a war setting (Call of Duty: Modern Warfare). Given the fact that COVID-19 can be considered a huge worldwide stressor, triggering fears and uncertainties [40], our findings suggest that a association between real-life stressors and settings chosen in video games could be present.…”
Section: Stream Countmentioning
confidence: 80%
“…Nostalgic experiences are characterized by recalling positive, meaningful events from the past that were typically experienced with close others (Wildschut, Sedikides, Arndt, & Routledge, 2006). Nostalgia can be triggered by psychological threats such as boredom (van Tilburg, Igou, & Sedikides, 2013), loneliness (Wildschut et al, 2006), meaninglessness (Routledge et al, 2011), or threats to authenticity (Baldwin, Biernat, & Landau, 2015), and incidental experiences such as smells (Reid, Green, Wildschut, & Sedikides, 2014), music (Cheung et al, 2013), movies, video game trailers (Natterer, 2014), and memories of playing games (Wulf, Bowman, Velez, & Breuer, 2018). Furthermore, nostalgia serves existential and social functions, meaning that it is a psychological resource (Sedikides, Wildschut, Routledge, & Arndt, 2015a) that contributes to psychological well-being (Baldwin et al, 2015;Baldwin & Landau, 2014).…”
Section: German Titlementioning
confidence: 99%